2020
DOI: 10.3389/fimmu.2020.01127
|View full text |Cite
|
Sign up to set email alerts
|

Durable Response and Good Tolerance to the Triple Combination of Toripalimab, Gemcitabine, and Nab-Paclitaxel in a Patient With Metastatic Pancreatic Ductal Adenocarcinoma

Abstract: Background: The performance of immune checkpoint inhibitor (ICI) monotherapy was proved to be disappointing in pancreatic ductal adenocarcinoma (PDAC). Increasing evidence has shown the promising efficacy of ICIs combined with systemic therapy in the first-line treatment in solid tumors. Case presentation: We reported a case of a metastatic PDAC patient who had a long-term partial response and good tolerance to the combined approach of toripalimab (a novel PD-1 inhibitor) and gemcitabine plus nab-paclitaxel (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…In a randomized phase II study involving 34 pre‐operative pancreatic cancer patients, high‐dose hydroxychloroquine combined with gemcitabine/nab‐paclitaxel was shown to increase the TME immune infiltration score, which is associated with significantly improved ( p < 0.0001) progression‐free and overall survival, compared to the results of 30 patients who received only gemcitabine/nab‐paclitaxel. Signs of enhanced anti‐PDAC efficacy for gemcitabine/nab‐paclitaxel using the PD‐1 antibodies toripalimab and pembrolizumab were evident in patients with a durable response 44 and a 100% disease control rate (27% PR + 73% SD) for 11 evaluable patients. 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized phase II study involving 34 pre‐operative pancreatic cancer patients, high‐dose hydroxychloroquine combined with gemcitabine/nab‐paclitaxel was shown to increase the TME immune infiltration score, which is associated with significantly improved ( p < 0.0001) progression‐free and overall survival, compared to the results of 30 patients who received only gemcitabine/nab‐paclitaxel. Signs of enhanced anti‐PDAC efficacy for gemcitabine/nab‐paclitaxel using the PD‐1 antibodies toripalimab and pembrolizumab were evident in patients with a durable response 44 and a 100% disease control rate (27% PR + 73% SD) for 11 evaluable patients. 45 …”
Section: Discussionmentioning
confidence: 99%
“…In a randomized phase II study involving 34 pre-operative pancreatic cancer patients, high-dose hydroxychloroquine combined with gemcitabine/ nab-paclitaxel was shown to increase the TME immune infiltration score, which is associated with significantly improved (p < 0.0001) progression-free and overall survival, compared to the results of 30 patients who received only gemcitabine/nab-paclitaxel. Signs of enhanced anti-PDAC efficacy for gemcitabine/nab-paclitaxel using the PD-1 antibodies toripalimab and pembrolizumab were evident in patients with a durable response44 and a 100% disease control rate (27% PR + 73% SD) for 11 evaluable patients 45. In light of the potential efficacy of Abraxane combined with immunotherapy, tens of clinical trials of this combinational regimen for patients with PDAC have been undertaken, as shown in the search results of the www.clini caltr ials.gov database using a search with keywords including pancreatic cancer, nab-paclitaxel and immunotherapy.…”
mentioning
confidence: 99%
“…Additionally, PD-L1 positive expression was detected in liver metastases in a patient with metastatic PC who had received toripalimab (240 mg Q3W) and gemcitabine (1000 mg/m 2 on day 1 and 8 every 3 weeks) plus nab-paclitaxel (125 mg/m 2 on day 1 and 8 every 3 weeks). As a result, he experienced long-term PR (8 cycles at the time of the report) but did not suffer any grade 3 or higher toxicity [ 38 ]. A phase Ib/II study in which toripalimab, gemcitabine, and nab-paclitaxel were combined to treat patients with nonresectable PC was initiated by the same center (ChiCTR2000032293, [ 39 ].…”
Section: Combination With Chemotherapymentioning
confidence: 99%
“…33 A case has reported that a patient with MPC has a long-term partial response and good tolerance to toripalimab plus gemcitabine and nab-paclitaxel. 34 Besides, a phase study found signi cant improved PFS and OS among patients with metastatic non-squamous NSCLC attributed to the addition of atezolizumab to bevacizumab, carboplatin and paclitaxel, which provide compelling evidence that the cancer-cell-killing effects of PD-1 blockade could be enhanced by immunoregulation mediated by cytotoxic chemotherapy and anti-angiogenesis. 35 Thus, combining toripalimab with cytotoxic nab-paclitaxel and small-molecule multi-receptor TKI may become a potential therapeutic strategy for LAPC or MPC patients.…”
Section: Introductionmentioning
confidence: 99%